Use of basic and specific pre-treatments for the biogas production. Revision and analysis - Martínez Hernández, Carlos Manuel; García López, Yaser (My University, 2016)
The present investigation is based on the importance of national and international biogas plants nowadays, which use animal manure as raw material; as well as agricultural and agribusiness residues for energy and biofertilizers production, minimizing the aspects of environmental contamination. This work is presented in three parts: firstly the technologies and methods to apply the basic and special pre-treatments to different biomasses in order to obtain their maximum potential of methane are described. Secondly, their particularities are detailed and finally, their possible utilization in the Cuban case is analyzed. As a result, it is shown the state of the art in the use of basic and special pre-treatments, to potentiate the increasing of methane production in agricultural or animal biomasses.

Teniendo en cuenta la importancia que tiene hoy en día la utilización de plantas de biogás a escala nacional e internacional, las cuales utilizan como materia prima excretas de origen animal; así como residuos agrícolas y agroindustriales para la producción de energía y biofertilizantes, minimizando los aspectos de contaminación medioambiental. Este trabajo se presenta en tres partes, en las cuales: primeramente se describen las tecnologías y los métodos para aplicar los pre tratamientos básicos y especiales a las diferentes biomasas con vistas a obtener su máximo potencial de metano. Una segunda parte donde se aborda las particularidades para llevar a efecto los mismos. Finalmente, una tercera parte donde se analiza su posible utilización en el caso cubano. Como resultado del mismo, se muestra el estado del arte en la utilización de pre tratamientos básicos y especiales, con el objetivo de potenciar el aumento de la producción de metano en biomasas de origen agrícola o animal
Utilización de pre-tratamientos básicos y específicos para la producción de biogás. Revisión y análisis
Keywords: Biogas; Basic Pre-treatments; Special Pre-treatments.; Pre-tratamientos Básicos; Pre-tratamientos Especiales.; Biogás